Model Peningkatan Komitmen Organisasi Pada Perguruan Tinggi Suwasta (PTS) Kota dan Kapupaten Serang Untuk Meningkat Kinerja Organisasi Secara Berkelajutan - Suryaman, Suryaman (Jurnal Manajemen, 2018)
Organizational commitment in higher education influences the quality and carrying capacity of the sustainability of an organization, in this case many analyzes are developed to measure organizational commitment, but not many discuss the model of the organization's own commitment to the sustainability of an organization that oversees the lecturer. This research was conducted as an effort to measure the commitment of organizations to support the sustainability of universities. A (PTS), the lecturer commitment assessment model was developed to see whether the commitment of lecturers had an influence on the sustainability of universities. The research method used was descriptive and verification of data samples of 275 PTS lecturers of City and Regency, Application of Structural Equation Model (SEM) was used to test models and hypotheses estimated using LISREL The results showed that leadership, motivation, job satisfaction, had a positive and significant effect to organizational commitment partially or jointly with a contribution of 60%, the dominating varabel is the motivation variable with a 0.44 dimension sign coefficient reflecting work motivation is the need for power of 0.85, while the variable that reflects the commitment of the lecturer is commitment normative as much as 0.83 researchers recommend that lecturer commitment can be increased especially through the work motivation of lecturers through the dimensions of power needs in PTS Serang City and regency.Keywords: Organizational commitment, leadership, motivation, job satisfaction ,.